Degradation of polyvinyl alcohol in textile waste water by Microbacterium barkeri KCCM 10507 and Paenibacillus amylolyticus KCCM 10508. Issue 4 (16th February 2016) - Chung, Jinwook; Kim, Seungjin; Choi, Kwangkeun; Kim, Jong-Oh
Abstract : Microbacterium barkeri KCCM 10507 and Paenibacillus amylolyticus KCCM 10508 were isolated and identified for the degradation of polyvinyl alcohol (PVA) contained in textile waste water. Kinetic parameters such as growth rate and substrate utilization rate were determined using a pure culture of two isolated strains. The degradation rate by a mixed culture of two isolated strains was higher than that by single strain only. Also, the effect of polymerization degree on biodegradation was negligible, but initial PVA concentration was very sensitive to biodegradation. Forty-two per cent of PVA and 55% of chemical oxygen demand in textile waste water were removed by a mixed culture of two isolated strains after 5 days.